INTEGRASI NILAI KEPESANTRENAN DALAM PERENCANAAN PENGEMBANGAN MADRASAH: STUDI ASESMEN KEBUTUHAN DI MA UBUDIYAH - Hadani; Rahman, Arif; Suhaimi; Sulistiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the integration of pesantren values in madrasah development planning through a needs assessment approach at MA Ubudiyah. The research employed a qualitative approach with a case study design to examine how pesantren values are identified and incorporated into institutional planning. Data were collected through in-depth interviews, observations, and document analysis involving the head of the madrasah, teachers, and coordinators of religious activities. Data analysis used the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings indicate that pesantren values such as sincerity (ikhlas), discipline, simplicity, and collective responsibility are integrated into the madrasah development planning process through three stages: identification of institutional needs, formulation of value-based development programs, and internalization of pesantren culture in educational and organizational practices. This integration strengthens the religious culture of the madrasah and supports the development of institutional identity and character-based education.